2011
DOI: 10.1371/journal.pone.0018392
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3 Complex Regulates Asymmetric Division and Cytokinesis in Mouse Oocytes

Abstract: Mammalian oocyte meiotic maturation involves oocyte polarization and a unique asymmetric division, but until now, the underlying mechanisms have been poorly understood. Arp2/3 complex has been shown to regulate actin nucleation and is widely involved in a diverse range of processes such as cell locomotion, phagocytosis and the establishment of cell polarity. Whether Arp2/3 complex participates in oocyte polarization and asymmetric division is unknown. The present study investigated the expression and functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 44 publications
11
116
0
Order By: Relevance
“…The roles of actin polymerization and various actin nucleators in spindle migration and asymmetric cell division in maturing oocytes have recently emerged 7,[27][28][29][30][31][32][33] ; however, the roles of other actin-binding proteins in oocyte maturation, including actin-capping proteins, ADF/cofilin, and tropomyosins, which are critical for the control of actin dynamics, are poorly understood. In this study, we present evidence that maintenance of cortical actin by Tpm3 is critical for spindle migration and polar body extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of actin polymerization and various actin nucleators in spindle migration and asymmetric cell division in maturing oocytes have recently emerged 7,[27][28][29][30][31][32][33] ; however, the roles of other actin-binding proteins in oocyte maturation, including actin-capping proteins, ADF/cofilin, and tropomyosins, which are critical for the control of actin dynamics, are poorly understood. In this study, we present evidence that maintenance of cortical actin by Tpm3 is critical for spindle migration and polar body extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…5 For example, various actin nucleators belonging to the formin family as well as the Arp2/3 complex are involved in the nucleation of actin filaments at the cortex. 6,7 To generate contractile force, actin filaments in the cortex form a complex with myosin II, 8 and this actomyosin complex controls how elastic or rigid the cell cortex is. 2 Tropomyosins are a family of coiled-coil rod-shape actin-binding proteins, and their roles in controlling the contraction of skeletal and smooth muscle have been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…LatA treatment removes all types of filamentous actin structures (Spector et al, 1983). To determine which actin-mediated process regulates Gef1 removal, we treated cells with CK666 to block only Arp2/3-mediated branched actin filaments (Sun et al, 2011). In these cells, Gef1-mNG removal was unhindered, as in DMSO-treated control cells, or localized to random sites along the cortex, but did not persist at the division site ( Figure 3C).…”
Section: Scd1 Promotes Gef1 Removal From the Division Site At The Endmentioning
confidence: 98%
“…27 During mouse oocyte meiotic maturation, actin was required for the chromosome migration, 9,28 cortical spindle anchorage, 29,30 cortex development and polarity establishment 2,31 and first polar body extrusion. 6,27 Additionally, some actin nucleation factors such as Arp2/3 complex, 6 Formin2 7,29 and Spire1/2 32 were involved in the actin organization during mouse oocyte maturation. Previous work showed that myosin II was activated by phosphorylation of its regulatory MLC at Ser19/Thr18, and the phosphorylation at MLC Ser19 was critical for actin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of activities of actin nucleators Arp2/3 and Formin 2 causes aberrant actin expression and the failure of polar body extrusion. 6,7 In addition, Cdc42, Ran and Rac1 are also involved in the regulation of cortical polarity during mouse oocyte maturation. [8][9][10] Although various molecules have been proposed to contribute to cortical polarity during oocyte meiosis, the pathways and mechanisms that modulate the meiotic apparatus remain to be determined.…”
Section: Introductionmentioning
confidence: 99%